Comparison study on characteristics of Microfibrillated Cellulose (MFC) extracted from cocoa pod husk and sugarcane bagasse - Jimat, Dzun Noraini; Zailani, Ima S.A.; ., Aviceena (Kulliyah of Engineering, International Islamic University Malaysia, 2016)

(untitled)
The aim of this study was to compare the characteristics extract microfibrillated cellulose (MFC) from cocoa pod husk (CPH) and sugarcane bagasses (SCB) via alkaline treatment and ultrasonication. Both sieved lignocellulosic materials were treated with 2% w/v sodium hydroxide (NaOH) for 5h at 80oC followed by bleaching with aqueous dilution of hydrogen peroxide at 75oC. Then, treated with 12% w/v NaOH at 80oC for 1h. Ultrasonication was conducted after completion of alkaline treatment to isolate fibrils aggregates. The average particle size of the obtained MFC from CPH and SCB were 0.286m and 1.333m respectively when ultrasonicated for 60s with 2 cycles. When the ultrasonication time was increased to 180s, the average particle of CPH was 3 times increased unlike SCB. Based on the SEM analyses, there were great difference of structure of crude samples after alkaline and ultrasonication treatments.